The Role of Music in the System of Spiritual Values and Culture of the Medieval Ancestors of Tatars - Salitova F.Sh. (Золотоордынское обозрение, 2021)
Research objectives: To reveal the specificity of folk and professional musical traditions and their moral and aesthetic significance in the life of the medieval ancestors of Tatars. Research materials: The study uses general scientific methods of analysis, synthesis, generalization, and the main methods of historical research – namely, the historical-comparative method and the method of historical periodization. Following the principle of historicism, the author analyzed a significant number of historical sources that reflect the development of musical culture among the ancestors of Tatars from its beginnings to the middle of the sixteenth century. Also, she used the results of archaeological and ethnographic research presented in monographs, articles, and other academic publications. Basic information about the development of musical culture among the medieval ancestors of Tatars is contained in the monuments of oral and written poetry (epic legends of the ancient Turks, the dastan “Idegey”, the poems of Muhammadyar, etc.), as well as in the notes of Arab and European travelers (Ahmed ibn Fadlan, Ibn Dasta, William of Rubruck, and John of Plano Carpini). Some aspects of this phenomenon are considered in a number of historical, musicological, and ethnomusicological studies (M. Khudyakov, L. Gumilev, M. Nigmedzyanov, G. Makarov, G. Saifullina, etc.). Results and novelty of the research: The study revealed that the origins of the musical traditions of the Tatar ethnos, formed mainly in the Middle Volga region, extend back to the common Turkic forms of artistic creativity. Later, music acted as an invariable attribute of socially significant and everyday forms of artistic activity (cult, court, military, folklore) of the Tatars’ ancestors in Volga Bulgharia, the Golden Horde, and Kazan Khanate. During the Middle Ages, there was an active development of diverse genres of both vocal and instrumental music. Its stable original basis was noticeably enriched with new intonations and rhythms emanating from the repertoire of musical traditions of various ethnic groups. A special mission in the spiritual life of society was carried out by the types and genres of spiritual and secular poetry closely related to music (chanting performances, including some with instrumental accompaniment). They functioned as an effective means for moral and aesthetic education, combining a variety of pedagogical functions with strong emotional impact. By the sixteenth century, the musical culture of the Tatar people formed into an integral, reified, and original system.